Penerapan Media Pembelajaran Teka-Teki Silang berbasis Aplikasi Eclipse Crossword untuk Meningkatkan Motivasi Belajar Siswa Kelas X E.6 Sekolah Menengah Atas Negeri Satu Kota Jambi - Setiawati Ningsih; Juliana Octaviani Manullang; Budi Purnomo; Lisa Rukmana; Muhammad Adi Saputra (Medan Resource Center, 2025)
This study aims to enhance students’ learning motivation in history courses through the implementation of a crossword-puzzle learning medium developed using the Eclipse Crossword application. The research employed a Classroom Action Research design conducted in Grade Ten, Phase E.6 of Sekolah Menengah Atas Negeri Satu Kota Jambi during the second semester of the 2023/2024 academic year, involving 35 students as research subjects. The study was carried out across two cycles, each consisting of two actions and following the stages of planning, implementation, observation, and reflection. Data were collected through classroom observations and student motivation questionnaires, and analyzed using both quantitative and qualitative descriptive techniques. The findings reveal a consistent increase in learning motivation across cycles, rising from 71% in Cycle I to 76% in Cycle II, and ultimately reaching 81% at the end of the intervention. The use of Eclipse Crossword proved effective in fostering enjoyable, interactive, and engaging history learning experiences that promoted greater student participation. These results indicate that application-based crossword media can be recommended as an innovative instructional strategy to improve learning motivation, particularly in history education at the secondary school level.